Using a Modified SERVQUAL Approach to Assess the Quality of Supply Chain Services in Greek Online Supermarkets - Anastasia D. Mitropoulou; Giannis T. Tsoulfas (Logistics, 2021)
Background: The purpose of this paper is to study customer satisfaction concerning orders from online supermarkets, which have recently boomed to fulfil the increased needs of customers during the COVID-19 pandemic. The service quality, as well as aspects of the logistics efficiency, are being examined, and the gaps between the expectations of people using these services and their perceptions about the received services are being evaluated. Methods: A modified approach of the well-known model SERVQUAL is suggested and used in the case of Greek online supermarkets. Thus, an initial contribution of this paper is the formulation of a framework which can be used to assess the quality of B2C logistics services. Results: The results show that customers’ expectations are exceeding their experiential perceptions in all the examined fields, and therefore there is room for substantial improvement. The study identified areas in which supermarkets’ online shops are close to meeting customer expectations and areas in which they fall far short. Conclusions: Competition is expected to become more intense and efficient supply chains that provide services of high quality will have a determinant role to play. Moreover, online supermarkets will have to rethink of their omni-channel structures to maintain and increase their market share. This is of particular importance during turbulent times such as the ones we are experiencing now.